Seismic soil classification of Italy based on surface geology and shear-wave velocity measurements. Issue 122 (July 2019) - Forte, Giovanni; Chioccarelli, Eugenio; De Falco, Melania; Cito, Pasquale; Santo, Antonio; Iervolino, Iunio
Abstract: During an earthquake the seismic wave amplification related to local site conditions can have a significant impact on the ground motion. In order to account for these local effects some proxies for the soil characteristics exist; e.g., the average shear-wave velocity of the upper 30 m ( V S, 30 ), or the equivalent shear-wave velocity from the ground to the depth of the seismic bedrock when this is less than 30 m V S, eq . The aim of this paper is to provide maps of seismic shallow soil classification for Italy accounting for two sources of information: site-specific measurements and large-scale geological maps. The soil maps are obtained via a four-step procedure: (1) a database of available site-specific investigations is built, covering (unevenly) the whole national territory; (2) twenty geo-lithological complexes are identified from the available geological maps; (3) the investigations are grouped as a function of the geo-lithological complex and the distribution of measured V S, 30 and V S, e q are estimated; (4) medians and standard deviations of such distributions are assumed to be representative of the corresponding complexes. The statistics of investigations are used to derive the large-scale soil maps. To make the results of the study available, a stand-alone software has been developed. Despite not being adequate substitutes of site-specific studies such as microzonation and local site response analyses, the provided results can be useful for large-scale seismic risk studies. Highlights: Procedure for correlating surface geological maps and Vs measurements. Maps of large-scale seismic soil classification for Italy. Site classification according to EC8 and ItBC2018. Stand-alone software for database interrogation.